The value of multiple tests of respiratory muscle strength. Issue 11 (8th June 2007) - Steier, Joerg; Kaul, Sunny; Seymour, John; Jolley, Caroline; Rafferty, Gerrard; Man, William; Luo, Yuan M; Roughton, Michael; Polkey, Michael I; Moxham, John
Abstract : Background: Respiratory muscle weakness is an important clinical problem. Tests of varying complexity and invasiveness are available to assess respiratory muscle strength. The relative precision of different tests in the detection of weakness is less clear, as is the value of multiple tests. Methods: The respiratory muscle function tests of clinical referrals who had multiple tests assessed in our laboratories over a 6-year period were analysed. Thresholds for weakness for each test were determined from published and in-house laboratory data. The patients were divided into three groups: those who had all relevant measurements of global inspiratory muscle strength (group A, n = 182), those with full assessment of diaphragm strength (group B, n = 264) and those for whom expiratory muscle strength was fully evaluated (group C, n = 60). The diagnostic outcome of each inspiratory, diaphragm and expiratory muscle test, both singly and in combination, was studied and the impact of using more than one test to detect weakness was calculated. Results: The clinical referrals were primarily for the evaluation of neuromuscular diseases and dyspnoea of unknown cause. A low maximal inspiratory mouth pressure (Pi max) was recorded in 40.1% of referrals in group A, while a low sniff nasal pressure (Sniff Pnasal) was recorded in 41.8% and a low sniff oesophageal pressure (Sniff Poes) in 37.9%. When assessing inspiratory strength with the combination of all three tests, 29.6% of patients had weakness. Using the two non-invasive tests (Pi max and Sniff Pnasal) in combination, a similar result was obtained (low in 32.4%). Combining Sniff Pdi (low in 68.2%) and Twitch Pdi (low in 67.4%) reduced the diagnoses of patients with diaphragm weakness to 55.3% in group B. 38.3% of the patients in group C had expiratory muscle weakness as measured by maximum expiratory pressure (Pe max) compared with 36.7% when weakness was diagnosed by cough gastric pressure (Pgas), and 28.3% when assessed by Twitch T10. Combining all three expiratory muscle tests reduced the number of patients diagnosed as having expiratory muscle weakness to 16.7%. Conclusion: The use of single tests such as Pi max, Pe max and other available individual tests of inspiratory, diaphragm and expiratory muscle strength tends to overdiagnose weakness. Combinations of tests increase diagnostic precision and, in the population studied, they reduced the diagnosis of inspiratory, specific diaphragm and expiratory muscle weakness by 19–56%. Measuring both Pi max and Sniff Pnasal resulted in a relative reduction of 19.2% of patients falsely diagnosed with inspiratory muscle weakness. The addition of Twitch Pdi to Sniff Pdi increased diagnostic precision by a smaller amount (18.9%). Having multiple tests of respiratory muscle function available both increases diagnostic precision and makes assessment possible in a range of clinical circumstances.